FUTURISTIC APPLICATION OF ARCHITECTURE ON THE FACADE OF A MIXED USED BUILDING - Mandaka, Mutiawati; Susanti, Anityas Dian; Sarasati, Carina; Sasmito, Adi; Khoirul Mustofa, M (Unika Santo Thomas, 2024)
This study evaluates the application of futuristic architecture on the facades of mix used buildings with a focus on three buildings in Paragon City Semarang, JHL Solitaire Serpong, and Pakuwon Surabaya. Mix used building is a building concept that integrates various functions such as residential, office, and business premises, with the aim of increasing space efficiency. This research uses a qualitative descriptive approach to identify how futuristic architecture is applied to the facades of these buildings. The results show that although there are efforts to apply the concept of futuristic architecture to elements such as doors, windows, walls, and light barriers by paying attention to proportion, rhythm, material, texture, and colour, the application is still limited. Paragon City Semarang, for example, only uses walls and light barriers with slight variations in proportion, while JHL Solitaire Serpong emphasises the use of light barriers that almost cover the entire building facade. Pakuwon Surabaya, on the other hand, features walls and glass windows with a large proportion of area. This research concludes that although the concept of futuristic architecture is trending, its implementation in the context of mixed used building facades is still not optimal, with variations between the three buildings studied.